2012
DOI: 10.1155/2012/623723
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of Selected Cameroonian Plants and Their Synergistic Effects with Antibiotics against Bacteria Expressing MDR Phenotypes

Abstract: The present work was designed to assess the antibacterial properties of the methanol extracts of some Cameroonian medicinal plants and the effect of their associations with currently used antibiotics on multidrug resistant (MDR) Gram-negative bacteria overexpressing active efflux pumps. The antibacterial activities of twelve methanol extracts of medicinal plants were evaluated using broth microdilution. The results of this test showed that three extracts Garcinia lucida with the minimal inhibitory concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 43 publications
6
36
0
Order By: Relevance
“…The presence of phenols in almost all the spices could be explained by the fact that they are mostly distributed in plants due to their important function in defense mechanisms [22]. Some of these results are in accordance with those obtained by Voukeng [17], Fankam et al [19], N'Guessan et al [23] and Lacmata et al [24] after a chemical screening of the same plants.…”
Section: Qualitative Chemical Screening Of the Methanolic Extractssupporting
confidence: 77%
“…The presence of phenols in almost all the spices could be explained by the fact that they are mostly distributed in plants due to their important function in defense mechanisms [22]. Some of these results are in accordance with those obtained by Voukeng [17], Fankam et al [19], N'Guessan et al [23] and Lacmata et al [24] after a chemical screening of the same plants.…”
Section: Qualitative Chemical Screening Of the Methanolic Extractssupporting
confidence: 77%
“…Our findings of antimicrobial activity corroborate the results of previous studies. [12,15,34] Certain R. stricta extracts (WAE, AN, AA and AN C ON) showed low activities against a limited number of strains (Table 3), a finding that Lacmata et al [35] also reported. These low activities could be due to mutations present in these multidrug-resistant bacteria that block or circumvent shared mechanisms of action of R. stricta extracts and other antibiotics.…”
Section: Resultsmentioning
confidence: 79%
“…According to Momo et al (2011), Dichloromethane sub-fraction from the methanol crude extract of the stem bark of G. lucida afforded eleven compounds namely putranjivic acid 1, methyl putranjivate 3, their intermediary lactone 2, friedeline 4, cycloartenol 5, 1,2-dihydroxy-xanthone 6, 1-hydroxy-2-methoxyxanthone 7, betulinic acid 8, oleanolic acid 9, β-sitosterol 10 and stigmasterol 11. Most of the isolated metabolites from the G. lucida are alkaloids, flavonoids, phenols and polyphenols, tannins, anthraquinones, steroids, saponins, glycosides (Lacmata et al, 2012;Ntie-Kang et al, 2013;Djacbou et al, 2014). At the Medical Institute of Medicinal Plants of Cameroon (IMPM, 1987), cycloartane derivatives and triterpene pentacycliane, anti-inflammatory and anti-acids active component were isolated from the leaves and bark of G. lucida.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, G. lucida extracts showed good antifungal activities on filamentous fungi. The antibacterial activities of twelve methanol extracts of medicinal plants were evaluated using broth microdilution by Lacmata et al (2012). The results of their test showed that extracts from G. lucida with the minimal inhibitory concentrations (MIC) varying from 128 to 512 µg/mL were one of the most active on all the 29 studied bacteria including MDR (multi drug resistance) phenotypes.…”
Section: Resultsmentioning
confidence: 99%